In search of a scaling scalar glueball - PEARDON, MICHAEL JAMES (Elsevier, 1999)
Anisotropic lattices are an efficient means of studying the glueballs of QCD, however problems arise with simulations of the lightest, scalar state. The mass is strongly dependent on the lattice spacing, even when a mean-field improved gluon action is used. The nature and cause of these errors are discussed and the scaling properties of the scalar from different lattice actions are presented.
PUBLISHED
Keywords: Pure & Applied Mathematics